2008
DOI: 10.1111/j.1523-536x.2007.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Exercise Support Program in Reducing the Severity of Postnatal Depression in Taiwanese Women

Abstract: The exercise support program given to postpartum women appeared to benefit their psychological well-being. This promising finding should be tested in a well-designed randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 18 publications
3
86
1
2
Order By: Relevance
“…Participants in the pramwalking group had signifi cant decreases in EPDS scores at weeks 6 and 12, but those in the social support group did not. In another study that also used the EPDS to assess changes in depressive symptoms [44], 80 women who had given brith 6 weeks earlier were randomly assigned to an exercise support or to a control group. Exercise support consisted of 1 h/wk of exercise at the hospital and another 2 hours of unsupervised, home-based exercise.…”
Section: Exercise In Depression During Pregnancy and Postpartummentioning
confidence: 99%
“…Participants in the pramwalking group had signifi cant decreases in EPDS scores at weeks 6 and 12, but those in the social support group did not. In another study that also used the EPDS to assess changes in depressive symptoms [44], 80 women who had given brith 6 weeks earlier were randomly assigned to an exercise support or to a control group. Exercise support consisted of 1 h/wk of exercise at the hospital and another 2 hours of unsupervised, home-based exercise.…”
Section: Exercise In Depression During Pregnancy and Postpartummentioning
confidence: 99%
“…(2) Postpartum fatigue, which is the result of the tense and overwhelming experience of caring for a newborn, has negative effects on the health of the mother, the neonate and the family. This phenomenon often begins immediately after delivery and reaches its maximum severity within 36 hours.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The changes involved during this period, including hormonal shifts and the beginning of new and unfamiliar child-rearing tasks, can cause primiparous mothers to experience stress and fatigue. (2) Postpartum fatigue, which is the result of the tense and overwhelming experience of caring for a newborn, has negative effects on the health of the mother, the neonate and the family. (3) This phenomenon often begins immediately after delivery and reaches its maximum severity within 36 hours.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated to have resonant clinical bene its, such as those evidenced by a controlled trial that looked at 3 hours of weekly exercise in depressed postpartum women and found that they improved signi icantly relative to controls 35 . Perhaps one of the putative mechanisms of this improvement is the effect of exercise on in lammatory cytokines, such as those demonstrated in the Treatment with Exercise Augmentation for Depression (TREAD) study, where depressed patients, partially treated with an antidepressant were found to have clinical improvement that correlated with decrease in THF-alpha.…”
Section: Exercisementioning
confidence: 99%